Red Blood Cells Elicit Platelet-Dependent Neutrophil Recruitment Into Lung Airspaces. Issue 2 (August 2021) - Arnold, Stephanie; Shah, Sajeel A.; Cleary, Simon J.; O'Shaughnessy, Blaze G.; Amison, Richard T.; Arkless, Kate; Page, Clive P.; Pitchford, Simon C.
Abstract : ABSTRACT: Hemolysis that occurs in intravascular hemolytic disorders, such as sickle cell disease and malaria, is associated with inflammation and platelet activation. Alveolar hemorrhage, for example following primary blast lung injury or acute respiratory distress syndrome, results in the escape of erythrocytes (RBCs) into alveolar spaces, where they subsequently lyse and release their intracellular contents. However, the inflammatory effects of RBCs in the airways are not fully understood. We hypothesized that RBCs in the airway induce an inflammatory response, associated with platelet activation. By instilling whole RBCs or lysed RBCs into the airways of mice, we have demonstrated that whole RBCs elicit macrophage accumulation in the lung. On the other hand, lysed RBCs induce significant inflammatory cell recruitment, particularly neutrophils and this was associated with a 50% increase in circulating platelet neutrophil complexes. Platelet depletion prior to lysed RBC exposure in the lung resulted in reduced neutrophil recruitment, suggesting that the presence of intracellular RBC components in the airways can elicit inflammation that is platelet dependent. To identify specific platelet-dependent signaling pathways involved in neutrophil recruitment, anti-P-selectin ligand and anti-PSGL1 blocking antibodies were tested; however, neither affected neutrophil recruitment. These findings implicate an involvement for other, as yet unidentified platelet-dependent signaling and adhesion mechanisms. Further understanding of how platelets contribute to lung inflammation induced by the presence of RBCs could offer novel therapeutic approaches to attenuate inflammation that occurs in conditions associated with alveolar hemorrhage.